THE SEMANTICS OF PROVERBS: HOW TO DEAL WITH “LITERAL” PROVERBS - Lemghari, El Mustapha (Proverbium - Yearbook, 2025)
The paper aims to pursue the debate on the semantics of proverbs. The focus is on the distinction between metaphorical proverbs and literal proverbs, as conceived and supported by Kleiber in a number of recent works. Kleiber’s main import consists in considering the mechanism he calls “superordinate and cross-domain figurativity” a prerequisite for proverbiality. Its operation as such on both kinds of proverbs results in two essential defining characteristics: (1) proverbial meaning is superordinate in character, and (2) it applies in an indirect way to instantiating cases. In view of this double characteristic, the distinction runs into a serious difficulty regarding the functioning of literal proverbs. It turns out to be hard to understand in this sense how literal proverbs can apply, despite their intrinsic literality, to a range of specific situations. We will argue from the perspective of class-inclusion theory for the metaphoricity of both kinds of proverbs, if only because of their similar functioning: every proverb is metaphorical in terms of both its superordinate meaning, which is quite different from its literal meaning, and its indirect cross-domain application.